Komunikasi dan Disposisi Penanganan Kekerasan Pada Perempuan dan Anak: Studi Kasus Pada Pelayanan Terpadu Perempuan dan Anak Kota Surakarta - Suci Amalia; Ismi Dwi Astuti Nurhaeni (Jurnal Mahasiswa Wacana Publik, 2021)
The Technical Implementation Unit for Integrated Services for Women and Children in the City of Surakarta is an institution formed as an effort by the local government of Surakarta to carry out the mandate of the Law and the efforts of the Surakarta city government to implement a Child Friendly City whose programs and activities promote and guarantee the rights and protection of children in carrying out its implementation. UPT PTPAS services are integrative, which can be in the form of one-stop services or networking or collaborating with other institutions related to handling violence against women and children. The research objective was to analyze the communication and disposition of the UPT PTPAS using Edward III's theory of public policy implementation. This research use desciptive qualitative approach. Methods of data collection through interviews and documentation. The data obtained were processed by analysis of Miles, Hubermen and Saldana (2014). The results showed that the communication that occurred was ineffective due to changes in the regulations that govern, while the disposition of the executor was well developed, this can be seen from the commitment of the executor and the response and understanding of the policy implementers in handling cases of violence that occurred against women and children in the city of Surakarta.